2009
DOI: 10.1002/uog.6289
|View full text |Cite
|
Sign up to set email alerts
|

Fetoscopic release of umbilical cord amniotic band in a human fetus

Abstract: Umbilical cord amniotic bands occur in approximately

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 8 publications
0
29
0
2
Order By: Relevance
“…In these two cases the amniotic bands were released successfully under ultrasound guidance 6 . Postoperative subchorionic bleeding and membrane separation, with amniotic fluid loss within the first 24 hours after surgery, seem to be directly related to this procedure 5,18 . PPROM has been reported to occur more frequently (57%) in cases of ABS than in those involving fetal endoscopic tracheal occlusion (FETO) or laser therapy for twin-twin transfusion syndrome in which membrane rupture occurs in 35% and 21% of cases, respectively 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…In these two cases the amniotic bands were released successfully under ultrasound guidance 6 . Postoperative subchorionic bleeding and membrane separation, with amniotic fluid loss within the first 24 hours after surgery, seem to be directly related to this procedure 5,18 . PPROM has been reported to occur more frequently (57%) in cases of ABS than in those involving fetal endoscopic tracheal occlusion (FETO) or laser therapy for twin-twin transfusion syndrome in which membrane rupture occurs in 35% and 21% of cases, respectively 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Kanayama et al [3] described the reversal of diastolic flow observed in a fetus with umbilical cord constriction due to amniotic bands. It is in cases like these that foetoscopic lysis of amniotic bands can be lifesaving [4].…”
Section: Discussionmentioning
confidence: 99%
“…Antenatal diagnosis of ABS is frequently difficult and is accurately diagnosed in only 29% to 50% of cases [6].Once diagnosed sonographically,umbilical cord constriction may be amenable to foetoscopic release in an attempt to avert fetal death. Fetoscopic release of umbilical cord amniotic band using YAG laser fibre has been reported [2]. …”
Section: Discussionmentioning
confidence: 99%
“…Amniotic bands occur in 1 of every 1,200-15,000 births and are demonstrable in1-2% of malformed infants [1].Nearly 10% of cases include umbilical cord strangulation [2].Here we report an unusual case of amniotic band syndrome were the amniotic band was attached to fetal head and the twisting of umbilical cord around this fibrous band lead to decrease fetal movement,fetal distress ultimately leading to fetal demise in second trimester, at 23 weeks.…”
Section: Introductionmentioning
confidence: 93%